Ship detection in Cyprus EEZ using Sentinel 1 data - Themistocleous, Kyriacos; Prodomou, Maria; Mettas, Christodoulos; Evagorou, Evagoras S.; Hadjimitsis, Diofantos G. (My University, 2020)
Marine Spatial Planning (MSP) is a key tool in managing the interaction of activities in the coastal and marine environment. It analyzes and allocates human activities to achieve the ecological, economic, and social goals established through a political process. Under this project, data was collected for various activities such as tourism, aquaculture, fisheries, renewable energy, ship routes, etc. This study focuses on the data referring to ship detection. Ship routes in Cyprus EEZ were created using position signals of ships in the EEZ for a temporal resolution of 15 minutes. These signals are compared to the positions of these ships using the radar backscatter derived from Sentinel-1A and Sentinel1B satellite images, which have a temporal resolution of 6 days. The radar backscatter for a certain period calculated using the Google Earth Engine platform, was then compared to the ship signals provided. This research is supported by the project entitled "Cross border Cooperation for Implementation of Marine Spatial Planning referred as THAL-CHOR 2"and is Co-funded by the European Regional Development Fund (ERDF) and by national funds of Greece and Cyprus under the Cooperation Programme Interreg V-A Greece-Cyprus 2014-2020.
Keywords: Cyprus; Google Earth Engine; Marine Spatial Planning; Remote Sensing; Sentinel-1; Ship detection